Lupus nephritis and its association with subclinical myocardial alterations in systemic lupus erythematosus assessed by cardiovascular magnetic resonance - Yang, Zhi; Wang, Ling-li; Zhang, Tian-yue; Wen, Miao; Zou, Hao; Zhu, Yong; Meng, Xue; Gao, Liang-chao; Fu, Bing; Pan, Shu-yue (Frontiers in Immunology, 2026)
BackgroundLupus nephritis (LN) is the most common and severe complication in patients with systemic lupus erythematosus (SLE) and is associated with cardiac disease. The purpose of this study was to assess the cardiac phenotype of SLE patients with LN using cardiovascular magnetic resonance (CMR), and to investigate whether comorbid LN is associated with left ventricular (LV) remodeling.MethodsClinical assessment and CMR were performed in 66 SLE patients without LN, 36 SLE patients with LN, and 20 age- and sex-matched healthy subjects.ResultsSLE patients with LN had a more impaired global longitudinal strain (-12.37 ± 5.15% vs. -14.40 ± 2.80% vs. -14.92 ± 3.04%; P = 0.045) than SLE patients without LN and control group. Moreover, native T1 (1330 ± 54 vs. 1286 ± 81 vs. 1256 ± 41; P<0.001), extracellular volume (ECV) (30.53 ± 4.57% vs. 28.34 ± 3.59% vs. 26.20 ± 3.03; P<0.001), and native T2 (43.69 ± 4.32 vs. 41.98 ± 3.66 vs. 39.60 ± 2.94; P<0.001) were higher in SLE patients with LN, intermediate in SLE patients without LN and lowest in control group. However, LV-LGE did not differ significantly between the SLE patients with or without LN (P > 0.05). In multivariable linear regression, LN status was associated with higher native T1 (β=0.244, P<0.05) and ECV values (β=0.224, P<0.05).ConclusionsSLE patients with LN showed more pronounced subclinical myocardial abnormalities on CMR. LN was an independent risk factor for cardiac impairment in patients with SLE.